Glucocorticoids Reduce Aberrant O-Glycosylation of IgA1 in IgA Nephropathy Patients - Kosztyu, Petr; Hill, Martin; Jemelkova, Jana; Czernekova, Lydie; Kafkova, Leona Raskova; Hruby, Miroslav; Matousovic, Karel; Vondrak, Karel; Zadrazil, Josef; Sterzl, Ivan; Mestecky, Jiri; Raska, Milan (Kidney & blood pressure research, 2018)
BACKGROUND/AIMS: IgA nephropathy is associated with aberrant O-glycosylation of IgA1, which is recognized by autoantibodies leading to the formation of circulating immune complexes. Some of them, after deposition into kidney mesangium, trigger glomerular injury. In patients with active disease nonresponding to angiotensin-converting enzyme inhibitors or angiotensin II blockers, corticosteroids are recommended. METHODS: The relationship between the corticosteroid therapy and serum levels of IgA, aberrantly O-glycosylated IgA1, IgA-containing immune complexes and their mesangioproliferative activity was analyzed in IgA nephropathy patients and disease and healthy controls. RESULTS: Prednisone therapy significantly reduced proteinuria and levels of serum IgA, galactose-deficient IgA1, and IgA-IgG immune complexes in IgA nephropathy patients and thus reduced differences in all of the above parameters between IgAN patients and control groups. A moderate but not significant reduction of mesangioproliferative potential of IgA-IgG immune complexes and IgA sialylation was detected. CONCLUSION: The prednisone therapy reduces overall aberrancy in IgA1 O-glycosylation in IgA nephropathy patients, but the measurement of IgA1 parameters does not allow us to predict the prednisone therapy outcome in individual patients.
Keywords: imunokomplex; Galactose deficiency; protilátky; Iga nephropathy; O-glycosylation; prognóza; Circulating immune complexes; Glycan-specific antibodies; Case-Control Studies; IgA nefropatie; Glucocorticoids; prednison; Antibodies; lidé; glukokortikoidy; studie případů a kontrol; Humans; Antigen-Antibody Complex; imunoglobulin A; Prednisone; Prognosis; IgA1 hinge region; glykosylace; Immunoglobulin A; Glycosylation; Glomerulonephritis, IGA